Flexibility vs. screening: The performance effects of temporary agency work strategies - Michael Beckmann; Dieter Kuhn (University of Basel, Center of Business and Economics (WWZ), 2012)
This paper empirically examines the impact of temporary agency work strategies on firm performance using panel data from German establishments. Thereby, special attention is devoted to the question, whether there are performance differences be- tween establishments using temporary agency workers (TAWs) as a buffer stock (flexibility strategy) and establishments testing TAWs for permanent positions (screening strategy). Theoretically, there are good reasons for using one strategy as well as adopting the other. On the other hand, however, both strategies may also be associated with serious drawbacks to be borne by the establishments. Our empirical analysis suggests that establishments following the flexibility strategy perform signifi- cantly worse than establishments following the screening strategy. Hence, we con- clude that employers act in their own interest, if they credibly consider temporary workers for permanent jobs instead of implementing a system of first- and second- class employees.
Keywords: C23; J24; J42; J82; M55; 330; Temporary agency work; firm performance; flexibility strategy; screening strategy; Leiharbeit; Unternehmenserfolg; Unternehmenswachstum; Deutschland